Simultaneous determination of two flavonoids based on disulfide linked β-cyclodextrin dimer and Pd cluster functionalized graphene-modified electrode1. Issue 75 (19th August 2015) - Ran, Xin; Yang, Long; Zhao, Genfu; Ye, Hanzhang; Zhang, Yanqiong; Fan, Shuangmei; Xie, Xiaoguang; Zhao, Hui; Li, Can-Peng
<x xml:space="preserve">Abstract</x> Illustration of the SS-β-CD–Pd@RGO nanohybrids simultaneously sensing baicalin and luteolin by an electrochemical strategy.